2016
DOI: 10.1080/01616412.2016.1238662
|View full text |Cite
|
Sign up to set email alerts
|

Association between anatomical variations of the posterior communicating artery and the presence of aneurysms

Abstract: Abnormal PCoAs (Types P-I and P-II) might be more vulnerable to PCoAA development, and Type P-II was the most vulnerable. There was a correlation between the angles of C7 and C6 part of the internal carotid artery and the presence of symptomatic PCoAA, with smaller angles being associated with increased frequency of symptomatic PCoAA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Hemodynamic stress is critical in the formation of aneurysms, leading to progressive degradation and inflammatory changes of arterial walls 13. Ultimately, anatomic variations in the PcoA may encourage the formation and rupture of PcoA aneurysms 11 14–16…”
Section: Discussionmentioning
confidence: 99%
“…Hemodynamic stress is critical in the formation of aneurysms, leading to progressive degradation and inflammatory changes of arterial walls 13. Ultimately, anatomic variations in the PcoA may encourage the formation and rupture of PcoA aneurysms 11 14–16…”
Section: Discussionmentioning
confidence: 99%
“…The ICA and the caudal part of the anastomosed branch of the nerve artery form the PCA ( 4 ). In the stage of 40 mm (8 weeks), the PCA appears as an extension of the posterior communicating artery (PComA) ( 5 ). The vertebra-basilar system is then formed and contributes to the blood supply of the PCA through the P1 segment.…”
Section: Introductionmentioning
confidence: 99%
“…During development, the diameter of the PCA-P1 segment gradually increases, while that of the PComA gradually decreases. At the time of birth, the PCA-P1 segment diameter is greater than that of the PComA, which represents the most common type known as the adult PCA ( 5 ). Stagnation in the process of embryonic development results in the following two cases.…”
Section: Introductionmentioning
confidence: 99%
“…Non-aneurysmal ICAs were more curved in women than men, which could explain the increased predisposition to aneurysm formation in women. Similarly, Hu et al ( 24 ) reported that the correlation between the angles at C7 and C6, the ICA, and the presence of symptomatic PcoA; with smaller angles being significantly associated with increased frequency of PcoA. Finally, Rosato et al ( 25 ) showed that ICA angulation at the PcoA origin is significantly higher in vessels harboring PcoA aneurysms when compared with non-aneurysmal ICAs.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies have investigated a possible correlation between adjacent vessels and the presence of aneurysms at the internal carotid artery ( 10 , 24 , 25 ). Adel et al ( 10 ) evaluated the mean and peak curvatures of the intracranial ICA and showed that the presence of sidewall aneurysms was highly correlated with curvature in all the genders.…”
Section: Discussionmentioning
confidence: 99%